2002
DOI: 10.1073/pnas.252652299
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for vestibular regulation of autonomic functions in a mouse genetic model

Abstract: circadian rhythm ͉ gravity ͉ temperature regulation ͉ Brn-3.1 ͉ parabrachial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 42 publications
6
40
0
2
Order By: Relevance
“…The result is an increased level of tonic vestibular discharge and in turn increased levels of activity in central vestibular relays (Fuller et al , 2004Kaufman et al 1992;Murakami et al 2002). Similar changes have been reported during space flight with increases and decreases in gravitational loading (Pompeiano et al 2001a, b).…”
Section: Discharge Rates and The Unloaded Maculasupporting
confidence: 60%
See 1 more Smart Citation
“…The result is an increased level of tonic vestibular discharge and in turn increased levels of activity in central vestibular relays (Fuller et al , 2004Kaufman et al 1992;Murakami et al 2002). Similar changes have been reported during space flight with increases and decreases in gravitational loading (Pompeiano et al 2001a, b).…”
Section: Discharge Rates and The Unloaded Maculasupporting
confidence: 60%
“…A swimming test (Jones et al 1999;Lim et al 1978;Ornitz et al 1998) was performed on each animal immediately prior to experiments. Normal swimming behavior was represented by the animal's ability to orient in a head-up position and swim comfortably.…”
Section: Animals and Surgical Preparationmentioning
confidence: 99%
“…Any inconsistency may be due to variable autonomic tone during electrocardiography in the previous studies; autonomic nervous activity was evaluated only in one [6]. Sympathetic activation through hearing stimuli is absent in SNHL children [22,23]. In our study, the sympathetic activity of the SHNL group may therefore be less than that in the control group, as evidenced by the decreased nLFP and lower RRI in the SNHL group (Table 1).…”
Section: Discussionmentioning
confidence: 64%
“…The vestibular system is primarily involved in gaze stabilization and postural control (23), but its influence has been expanded to autonomic and bone regulation (11,61,63), spatial learning and memory (5, 6, 56), and spatial orientation and perception of gravitational verticality (37). Studies carried out in environments in which gravity is altered have shown evidence of a possible influence of the vestibular system on hypothalamic circadian function in rats (27) and mice (18,46 …”
mentioning
confidence: 99%
“…The vestibular system is primarily involved in gaze stabilization and postural control (23), but its influence has been expanded to autonomic and bone regulation (11,61,63), spatial learning and memory (5,6,56), and spatial orientation and perception of gravitational verticality (37). Studies carried out in environments in which gravity is altered have shown evidence of a possible influence of the vestibular system on hypothalamic circadian function in rats (27) and mice (18,46); disruption of circadian rhythms of temperature (Temp) and locomotor activity (Act) have been similarly observed in both species for about 7 days in a 2 G environment generated by a centrifuge. Knockout mice devoid of otolithic vestibular sensors [het(Ϫ/Ϫ) mice] remained unaffected by hypergravity at 2 G (18).…”
mentioning
confidence: 99%